ECOENZYME EDUCATION AS A SOLUTION TO REDUCE HOUSEHOLD ORGANIC WASTE IN HULUNG VILLAGE - Ernawati Hatuwe; Mirdat Hitiyaut; Rahma Tunny (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
Waste is a major problem facing Indonesian and global communities. Poorly managed household organic waste can lead to environmental pollution and public health problems. One environmentally friendly solution is the use of ecoenzymes, a liquid fermented from organic waste that is beneficial for hygiene and simple farming. This community service activity aims to improve the knowledge and skills of the Hulung Hamlet community in processing organic waste into ecoenzymes as an effort to reduce household waste volume. Implementation methods include education through outreach, interactive discussions, and live demonstrations of the ecoenzyme production process using readily available organic materials. Evaluation was conducted through participant observation and increased understanding before and after the activity. The results of the community service show an increase in community knowledge about the benefits of ecoenzymes and the ability of participants to practice ecoenzyme production independently. Furthermore, there has been a change in community attitudes, leading to greater concern for organic waste management. The recommendations from this activity are the need for continued mentoring and the sustainable implementation of ecoenzymes to support a cleaner and healthier environment in Hulung Hamlet.